1981
DOI: 10.1055/s-2008-1037362
|View full text |Cite
|
Sign up to set email alerts
|

Aborteinleitungen im zweiten und dritten Trimenon mit »Sulproston«

Abstract: Report on 114 terminations of pregnancy during the second and third trimester of pregnancy with a new prostaglandin E2 derivative "Sulprostone". In 84 cases legal therapeutic abortions were induced. In 30 women an abnormal pregnancy was terminated. "Sulprostone: is a prostaglandin with selective activity in the uterus. It can be administered parenterally or locally. 48 women received intravenous sulprostone, 35 patients had extraamniotic injections and 31 patients had extra-amniotic injections following an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Nach intrazervikaler Prostaglandin-E 2 -Applikation sind Zervixverletzungen infolge des Primingeffekts sehr selten; Stampe Sorensen et al [33] und Herabutya und Israngura Na Ayudthaya [2] wiesen in ihren Untersuchungen keine Zervixverletzungen nach, Schmidt und Ditz [34] registrierten lediglich bei einer Patientin eine Läsion der Zervix. Zervixverletzungen wurden in Einzelfällen auch bei der extraamnialen Prostaglandin-E 2 -Applikation beschrieben [25,26,28,30,32,35]. Bei D&C hingegen resultieren Zervixverletzungen häufig aus einer forcierten und zu raschen Dilatation des Zervikalkanals mit Hegar-Stiften bei unreifer Portio oder -was in unserer Gruppe die Hauptursache war -aus dem Ausreissen der Kugelfasszangen.…”
Section: Introductionunclassified
“…Nach intrazervikaler Prostaglandin-E 2 -Applikation sind Zervixverletzungen infolge des Primingeffekts sehr selten; Stampe Sorensen et al [33] und Herabutya und Israngura Na Ayudthaya [2] wiesen in ihren Untersuchungen keine Zervixverletzungen nach, Schmidt und Ditz [34] registrierten lediglich bei einer Patientin eine Läsion der Zervix. Zervixverletzungen wurden in Einzelfällen auch bei der extraamnialen Prostaglandin-E 2 -Applikation beschrieben [25,26,28,30,32,35]. Bei D&C hingegen resultieren Zervixverletzungen häufig aus einer forcierten und zu raschen Dilatation des Zervikalkanals mit Hegar-Stiften bei unreifer Portio oder -was in unserer Gruppe die Hauptursache war -aus dem Ausreissen der Kugelfasszangen.…”
Section: Introductionunclassified
“…However, when it was observed that the oxytocic effect was complemented by cervical dilatation in induction of second-trimester abortions, it was natural to consider exploiting this cervical and softening effect in first-trimester terminations as well. Thus, an attempt was made to replace mechanical dilatation by a chemistry-based method, in our case by prostaglandin (5,11).…”
Section: Introductionmentioning
confidence: 99%